Analisis Kemampuan Kreativitas Matematis Siswa Kelas IV Pada Materi Bagun Datar di SDIT An-Nahl Kabupaten Aceh Tengah - Harahap, Rosliana; Qomariyah Ahmad, Nurul (EL-Hadhary: Jurnal Penelitian Pendidikan Multidisiplin, 2024)
Students' mathematical creativity or mathematical creative thinking abilities are the abilities possessed by students to solve mathematical problems. A student who has mathematical creativity abilities will be able to find new ideas and ideas in finding solutions to mathematical problems. Indicators of students' mathematical creativity abilities used in research are fluency, flexibility, originality and elaboration. The aim of this research is to analyze students' mathematical creativity abilities in flat shape material, namely in class IV elementary school. This type of research is qualitative descriptive research. Data collection techniques were through observation and tests, with instruments as observation guidelines and written tests in the form of descriptions given to class IV students at SD IT An-Nahl. Data analysis through stages of reduction, data presentation and drawing conclusions. The results of the research show that students' mathematical creative thinking abilities in flat shape material are still low. Some students have problems with the elaboration indicator, which can be seen from their low scores compared to other indicators. Indicators of original thinking, the answers given by all students were all correct. Almost the majority of students experience problems with the average student flexibility indicator. To improve students' mathematical creativity abilities, students must be accustomed to working on creative thinking ability questions.